Conserved cluster organization of insect Runx genes. - Bao, R.; Friedrich, M. (Development genes and evolution, 2008)
Runx gene family transcription factors play important regulatory roles in metazoan development. The Drosophila genome contains four Runx genes, two of which are well studied (runt and lozenge) and two of which have not been explored in depth yet (CG42267 and CG34145). In the absence of paralog-specific orthologs in vertebrates, we investigated the evolutionary conservation of the Drosophila Runx genes in the genomes of mosquito, red flour beetle, honeybee, and distantly related Bilateria. All four Drosophila Runx genes are conserved in other endopterygote insects. Strikingly, their genetic linkage and genomic arrangement is also highly conserved despite past recombination events in the same genomic region. The preservation of Runx gene cluster organization for at least 300 million years resembles that of insect Hox and selected Wnt genes. We propose a model for the conserved cluster organization of developmental gene family paralogs based on differential coduplication of regulatory elements that act over long distances.